ผลลัพธ์ของการจ่ายยารักษาโรคเบาหวานต่อเนื่องโดยเภสัชกรในศูนย์สุขภาพชุมชนตลาดเกรียบ - สการินทร์ มีสมพืชน์ (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
Objectives : The study was to determine the clinical outcomes and drug related problems (DRPs) in diabetic patients after received drug refilling by pharmacist. Methods : The diabetic patients received drug refilling by pharmacist and were followed up for a period of three months. The study was conducted during December 2008 to March 2009. The patients met pharmacist for refilling, education, medication counseling, monitoring, and management. The evaluation was done by comparing the clinical outcomes of patients based on assessment of blood glucose, blood pressure, lipid profiles, renal function and outcomes of drug related problems before and after drug refilled by pharmacist. Results : Forty-one patients completed the study. There were 37 women and 4 men with a mean age of 64.00 ± 8.81 years. The patients had no significantly differences in hemoglobin A1C and fasting plasma glucose levels before and at the end of the study (p = 1.000 and p = 0.267 ,respectively). However, the percentage of patients who had target A1C increased from 36.6% to 48.7%. The total cholesterol (p = 0.000) were reduced to target at the end of study. The patients had no significantly differences in target blood pressure (p = 0.143), low density lipoprotein (p = 0.096), blood urea nitrogen (p = 0.250) and creatinine (p = 0.625). The pharmacist can detected 185 DRPs. Most of them were needs additional drug therapy (38.4%), dosage too low (23.7%) and noncompliance (18.3%). Seventy-five problems (40.6%) were resolved by pharmacist and 110 problems (59.4%) had to consult with the physician. Conclusions : The study demonstrated that the antidiabetic drug refilling by pharmacist at primary care unit achieved an improvement in A1C and total cholesterol of patients and could resolve the number of drug related problems